Pengembangan Kurikulum di Madrasah Aliyah Ulul Albab Kota Lubuk Linggau - Sartika, Devi; Kusen; Sumarto; Darmansyah, Rafik (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
This research aims to describe several important aspects related to the Madrasah Aliyah Ulul Albab curriculum before development, during the curriculum development process, and the impact of curriculum development in improving the quality of education. The research approach used is qualitative using a phenomenological approach, which focuses on understanding curriculum development activities at MA Ulul Albab. This research takes the form of a case study with a single approach, with a single data analysis. In carrying out this research, researchers used various data collection techniques, including observation, interviews, and documentation. Research informants involved various parties within MA Ulul Albab, such as the school principal, deputy head of curriculum, school committee, Islamic boarding school administrators, deputy head of student affairs, and homeroom teachers from various levels. To ensure the validity of the data, researchers carried out triangulation and peer checking through discussions. The research results show that the Madrasah Aliyah Ulul Albab curriculum before development was an integrity curriculum which was the result of a combination of the 2013 Curriculum (K-13) with the Islamic boarding school curriculum. Curriculum development is carried out optimally, implementing K-13, implementing the semester credit unit system (SKS), and meeting Content Standards and Graduate Competency Standards (SKL). In the development process, MA Ulul Albab uses Information and Communication Technology (ICT) media as a learning tool and utilizes online media to access lessons.